A Systematic Review Of Green Roof Technology Using Coco Peat As A Substrate - Manan, Faten Nur Diyana Abdul (Universiti Sains Malaysia, 2021)
This review was conducted to study the design of green roof using coco-peat as substrate. Generally, the green roof concept was implemented to support plant growth while also giving aesthetic, environmental, and economic benefits. It has been around for over a century and have become one of the most important components in urban areas in recent decades. Green roof is categorized into three parts which is intensive, semi-intensive and extensive. Meanwhile, coco peat is an organic and renewable substrate processed from coconut shells. It has good planting performance and reusable. It is mostly used as a substrate because of its high Water Holding Capacity up to 100% , Air-Filled Porosity (13%) and Bulk Density of 0.08g/cm3. The objectives of this study are to determine the effectiveness of coco-peat as substrate on green roof for the attenuation of stormwater and reducing peak flow. Next, to examine the effectiveness of coco peat as substrate in improving stormwater quality. Therefore, most of the articles reviewed is focused on topic of green roof substrate. The review conducted proved that coco peat is effective to attenuate stormwater and reducing peak flow as it has high Water Holding Capacity to retain stormwater up to 100%. It was also proved that by using coco peat as substrate can improve stormwater quality as it able to remove heavy metals and pollutants by adsorption up to 99% removal rate. Lastly, it is also an organic matter and renewable substrates, so coco peat is a sustainable to be used for green roof technology as it can easily accessible in some countries for example Malaysia.